The triple burden of obesity, HIV, and anaemia during pregnancy and associations with delivery outcomes in urban South Africans - Alessandra Prioreschi; Stephanie V Wrottesley; Linda Adair; Kate A Ward; Shane A Norris (The South African Journal of Clinical Nutrition)
Objectives: First, to explore the independent associations between obesity, HIV (with ARV treatment), and anaemia and delivery outcomes in urban South African women and, second, to identify any potential interactions between these co-morbidities.Design: Longitudinal observational cohort study.Setting: Soweto, South Africa.Subjects: Mother–infant pairs (789) were recruited when mothers were < 20 weeks pregnant.Outcome measures: Infant gestational age at delivery was calculated, and infant birth weight and length were measured by trained research nurses. Head circumference was measured using a metal head circumference tape measure. Multivariable linear regression and logistic regression models were used to test the associations between obesity, HIV-positive status, and anaemia and delivery outcomes, as well as the potential interactions between the triple burden exposures.Results: At baseline, 14%, 11%, and 22% of women were diagnosed with only obesity, HIV, or anaemia respectively, while 42% had two conditions and 5% were exposed to the triple burden. Maternal obese vs. non-obese status was associated with a 0.32 higher weight-to-length z-score at birth (p < 0.01) and a 2.93 times higher risk of a large-for-gestational age delivery (p < 0.01). There were no interactions between the triple burden exposures on delivery outcomes.Conclusions: This study presents evidence for the importance of prioritising obesity prevention prior to conception in urban African settings such as South Africa. In addition, our findings highlight the need for more research into the complex relationships between maternal co-morbidities, as well as their potential influence (alone and in combination) on maternal and offspring health in the short and longer term.